(x-4)2=(x-2)2

Simple and best practice solution for (x-4)2=(x-2)2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)2=(x-2)2 equation:


Simplifying
(x + -4) * 2 = (x + -2) * 2

Reorder the terms:
(-4 + x) * 2 = (x + -2) * 2

Reorder the terms for easier multiplication:
2(-4 + x) = (x + -2) * 2
(-4 * 2 + x * 2) = (x + -2) * 2
(-8 + 2x) = (x + -2) * 2

Reorder the terms:
-8 + 2x = (-2 + x) * 2

Reorder the terms for easier multiplication:
-8 + 2x = 2(-2 + x)
-8 + 2x = (-2 * 2 + x * 2)
-8 + 2x = (-4 + 2x)

Add '-2x' to each side of the equation.
-8 + 2x + -2x = -4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-8 + 0 = -4 + 2x + -2x
-8 = -4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-8 = -4 + 0
-8 = -4

Solving
-8 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 | | -[4(7)-(14(7)+8)]=8+(9(7)+7) | | 6+(-10)+(-2)+8= | | -12.1+.5=0.9p+5.3 | | -12+.5=0.9p+5.3 | | 3c+12=6c+11.31 | | 3c+12=6c+12.31 | | -5-2=1-2x+3x | | 2.3x+1.37=-11.74 | | -[4z-(14z+8)]=8+(9z+7) | | -91.9+n=-99 | | 0=-u+u | | -8(t-2)-(t+3)=10 | | 7y=21x+14 | | 3r-5(12)=-22 | | 0.7x-0.6x+1=4 | | -10y+18=15y+13 | | -10y+18=15y+13-8 | | 1.2x-1.2=8.4 | | x+2y=51 | | -2y-3y+8=8-512 | | 9x+4y=-2 |

Equations solver categories